Association Between Length of Work Experience and Spiritual Intelligence Among Adult Medical–Surgical Nurses: A Cross-Sectional Study - Suwardianto, Heru; Santoso, Teguh; Mahyuvi, Tata; Alfianto, Ahmad Guntur; Amaral, Octavio Daniel Bria; Pinto, Joaquim; Kumar, Sesha (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Spiritual Intelligence (SI) is essential for nurses caring for critically ill surgical patients. Previous studies suggest work experience may influence SI, but the extent and specific dimensions affected remain unclear. This study addresses this gap by analyzing the relationship between work experience and four SI dimensions: Critical Existential Thinking (CET), Personal Meaning Production (PMP), Transcendental Awareness (TA), and Conscious State Expansion (CSE) Methods: A cross-sectional study was conducted among 35 nurses working in adult surgical wards at two public hospitals in Kediri, Indonesia. Inclusion criteria were registered nurses with at least six months of experience in surgical wards; exclusion criteria were nurses on leave or with incomplete data. Purposive sampling was used. Independent variable: work experience (years); dependent variable: spiritual intelligence measured using the Spiritual Intelligence Self-Report Inventory (SISRI-24). Data analysis followed the STROBE guideline and was performed using Lambda tests with α < 0.05. Descriptive statistics were reported for key variables, including mean work experience Result: The mean work experience of participants was 7.3 ± 4.1 years. Work experience was significantly associated with Personal Meaning Production (PMP) (p = 0.034) and Conscious State Expansion (CSE) (p = 0.007), indicating that nurses with longer experience are better able to find life meaning and expand spiritual awareness. No significant relationships were observed for Critical Existential Thinking (CET) and Transcendental Awareness (TA). Conclusion: Work experience positively influences certain SI dimensions (PMP and CSE) but not others (CET and TA). These findings suggest that additional factors, such as education, personal experiences, and workplace environment, contribute to SI development. Practical implications: Healthcare institutions should implement spiritual reflection and mindfulness training to support nurses’ well-being. Future research should include larger samples and explore cultural and intervention-based influences on SI development.